Analisis Efektivitas Penggunaan Media Pembelajaran Digital Ditinjau dari Aspek Pemecahan Masalah Matematis - Vivi Sakta Tri Rahmadona; Nur Fitriyana; Khathibul Umam Zaid Nugroho (Proceeding of Silampari Conference of Life Science and Technology, 2026)
The integration of digital educational tools in the teaching of mathematics is increasingly common; however, studies focusing on its application in terms of mathematical problem-solving are fragmented and have not been comprehensively organized. This research seeks to investigate the features of digital educational tools in mathematics content, evaluated through mathematical problem-solving indicators among elementary, middle, and high school learners, as well as university-level students. The approach taken is a Systematic Literature Review (SLR), which consists of six phases, starting with formulating the Research Question, defining Selection Criteria, creating a Search Strategy, selecting Studies, assessing the Quality of Studies, and finally, Synthesis Result, utilizing PICOC (Population, Intervention, Comparison, Outcome, and Context) analysis to systematically identify and assess pertinent journal articles. Out of the 71 articles discovered, 12 were judged to be relevant to this research. The results indicate that digital educational tools have been shown to be effective in helping to improve and deepen students' mathematical problem-solving skills, all while incorporating technology into the educational experience. Therefore, digital educational resources positively affect learning by enhancing comprehension, fostering engagement, and connecting mathematical principles to students' everyday experiences.